METHOD OF TEACHING ENGLISH IN TECHNICAL SCHOOLS - Saminova Nodira Mukhtar qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: in this article the right methods of teaching English for students of technical schools. Specified teaching methods are mostly discussed in this article. We look at the problem connected with methods of teaching English to international students in technical schools of higher education. Our research is focused on the solution of problems connected with teaching English in the field-specific terms to students in technical schools of higher education.